Dealing with neonatal emergencies in low-resource settings. Issue 6 (December 2019) - Shukla, Vivek; Mwenechanya, Musaku; Carlo, Waldemar A.
Abstract: We describe the development and delivery of neonatal care including trends and impacts of major interventions on neonatal mortality particularly in low-resource settings. Low- and middle-income countries continue to be major contributors to neonatal mortality. Although there has been progress in reducing neonatal mortality, neonatal deaths are contributing an increasing percentage of childhood mortality. Several interventions targeting neonatal care such as neonatal resuscitation and essential newborn care have contributed to improved outcomes. However, there are still many neonatal deaths that are preventable with known effective interventions. This review addresses interventions proven effective in reducing neonatal mortality, challenges to implement them, and future directions of implementing these interventions in low- and middle-income countries. Highlights: Low- and middle-income countries have disproportionately high numbers of neonatal mortality and morbidity. Several low-cost and high-impact intervention packages can improve neonatal outcomes in low- and middle-income countries. Deaths from preventable serious morbidities will continue to burden society unless gaps in healthcare provision are met.